Wave climate pattern, storms and extremes for Northern Djerba Island (South-East Tunisia) - Halouani, Nabila; Amarouche, Khalid; Akpınar, Adem (Natural Hazards, 2026)
This study presents the first investigation of the nearshore wave climate in the main tourist area on the northern coast of Djerba Island, southeast Tunisia. The region is known for its long, dynamic sand spit at Ras Rmel, and its low-lying sandy beaches, which are experiencing significant long-term erosion driven by coastal processes. These beaches face threats from extreme winter storms and rising sea levels, exacerbating coastal risks. Accurate estimation of mean and extreme wave characteristics is crucial for assessing erosion and flooding risks under extreme weather conditions and improving coastal protection structures. In the absence of buoy wave measurements along the Djerba coastline, a numerical wave modelling approach was applied. The third-generation SWAN wave model, operating in a nested grid with a high spatial resolution was implemented and validated using altimeter data from seven satellites. Based on the produced hindcast data, the characteristics of wave storm events and the extreme wave return periods were assessed. The results show that the Djerba coastline experienced a significant number of storms (116 events) between 2011 and 2020, with frequent storms coming from the east, northeast, and east-northeast directions. The most severe storms, in terms of intensity and duration, occurred in 2019, driven by easterly winds. Nearshore wave modelling results revealed that the central part of Djerba beach is particularly exposed during extreme wave events, and may be more vulnerable to erosion and flooding.
Keywords: Djerba Island; Extremes; Storms; Tunisia; Wave climate pattern